The scope and legal forms of municipal entrepreneurship in interwar Poland and currently - Bartosz Kołaczkowski; Małgorzata Ratajczak (Prawo Budżetowe Państwa i Samorządu)
In this study we have addressed a problem of a development of legal solutions concerning the scope and forms of a self-government entrepreneurship in Poland. The history of the self-government entrepreneurship in Europe dates back to the first half of the 19th century, and in free Poland - the period of the Second Republic of Poland. During the interwar period, issues related to a self-government entrepreneurship gained a lot of controversy in literature. This is also a case in present days. The analysis showed that in the period of the Second Republic of Poland (when discussions about the legitimacy of running public enterprises were under way), local self-government units had a much broader scope of freedom in conducting self-government entrepreneurship than today. This is an outcome of an introduction in current legislation of bans and limitations on entrepreneurship of a self-government authorities, which apply to cases when the economic activity of local government goes beyond the sphere of public interest.